2012
DOI: 10.1102/1470-7330.2012.9022
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific contrast agents

Abstract: In the patient with cancer, magnetic resonance imaging is increasingly used as a diagnostic tool for disease detection, lesion characterization, as well as the assessment of treatment response. Although non-contrast T1-weighted and T2-weighted imaging, together with low molecular weight extracellular gadolinium contrast-enhanced T1-weighted magnetic resonance imaging remain the cornerstone for liver assessment, there is increasing recognition of the benefits of liver-specific contrast agents for disease evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…50 Ironoxide nanoparticles of this size localise in the liver via phagocytosis into the Kupffer cells and malignant liver legions often lack normal Kupffer cells and remain "bright" in an MRI scan upon SPION administration. 51,52 However, the lower MRI sensitivity means that differentiation between regions with and without SPION may be challenging and may limit widespread clinical utility. Clinical utility could be increased by using PET radioisotope labelled SPIONs such as those developed in this study due to the increased sensitivity of PET and subsequent clarity of low uptake regions.…”
Section: In Vivo Imaging Biodistribution and Stabilitymentioning
confidence: 99%
“…50 Ironoxide nanoparticles of this size localise in the liver via phagocytosis into the Kupffer cells and malignant liver legions often lack normal Kupffer cells and remain "bright" in an MRI scan upon SPION administration. 51,52 However, the lower MRI sensitivity means that differentiation between regions with and without SPION may be challenging and may limit widespread clinical utility. Clinical utility could be increased by using PET radioisotope labelled SPIONs such as those developed in this study due to the increased sensitivity of PET and subsequent clarity of low uptake regions.…”
Section: In Vivo Imaging Biodistribution and Stabilitymentioning
confidence: 99%
“…Our retrospective study showed that gadoxetic acid-enhanced MRI identified additional lesions in the evaluation of liver metastasis as previously reported. 17 However, our study challenges the clinical value of using these liver specific contrast agents in all patients in the preoperative setting. In fact, our results show that patients with a unique and large hepatic lesion on the standard MRI did not have their surgical management altered by the addition of a gadoxetic acid-enhanced MRI.…”
Section: Discussionmentioning
confidence: 81%
“…These molecules present a biphasic enhancement pattern; the first phase, immediately after intravenous injection, is similar to CT dynamic enhancement after iodine contrast injection while a delayed phase occurs after 10 to 120 min after injection[ 10 , 11 ]. Lesions not containing hepatocytes cannot take up such molecules; therefore, metastasis appear hypointense compared with surrounding healthy liver parenchyma[ 12 ].…”
Section: Magnetic Resonance Protocolsmentioning
confidence: 99%
“…Hepatobiliary-reticuloendothelial phases are T1W sequences, with or without fat-sat, if Gd-BOPTA or Gd-EOB-DTPA, both increasing T1 relaxivity, have been administered[ 12 , 19 ]. Proton density or T2W sequences are used with SPIOs contrast agents[ 12 , 19 ].…”
Section: Magnetic Resonance Protocolsmentioning
confidence: 99%
See 1 more Smart Citation